(untitled) (gjstudies, 2014)
This research investigates the transformative role of public sector accountingreforms in enhancing fiscal accountability, a critical yet underexplored nexus ingovernmental financial management. Moving beyond conventional studies thatoften treat accounting reforms as mere technical adjustments, this paper positsthem as fundamental institutional reconfigurations that reshape the very architecture of fiscal governance. The study’s novelty lies in its conceptual framework,which synthesizes principles from institutional theory, public administration, andaccountability scholarship to analyze reforms not as isolated events but as dynamicprocesses embedded within specific political and administrative contexts. We argue that the efficacy of accrual accounting, performance budgeting, and integratedfinancial management information systems (IFMIS) in promoting accountability iscontingent upon their alignment with broader governance ecosystems, including legal frameworks, political will, and administrative capacity. Through a qualitativemulti-case study analysis of reform trajectories in three distinct jurisdictions, theresearch uncovers the complex, often non-linear, pathways through which accounting innovations influence transparency, answerability, and enforcement mechanisms.The findings reveal that successful reforms act as ’accountability catalysts,’ creating virtuous cycles of improved information quality, strengthened oversight, andenhanced public trust. Conversely, technically sound but contextually misalignedreforms can engender ritualistic compliance and accountability deficits. The paperconcludes by proposing a contingency model for designing and implementing publicsector accounting reforms, offering original insights for policymakers and scholarsaiming to harness financial management innovations for deeper democratic accountability and fiscal sustainability.